Duszpasterze późnej starożytności (VI-VII w.) o wychowaniu dzieci - Wygralak, Paweł (Poznańskie Studia Teologiczne, 2010)
The article presents the teaching of the pastors of late antiquity (6th-7th c.): Caesarius of Arles, Eligius of Noyon and Ildephonsus of Toledo, on the Christian education of children, a process in which parents and godparents play a special role. They fulfill their obligation not only by instruction but above all by the example of a good life. The ultimate goal of education is the eternal happiness of the children as well as the parents and godparents. Also school is seen as an important factor in the educational process.